2012
DOI: 10.1371/journal.pone.0051683
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Mathematical Model of Cardiomyocyte Turnover in the Adult Human Heart

Abstract: RationaleThe capacity for cardiomyocyte regeneration in the healthy adult human heart is fundamentally relevant for both myocardial homeostasis and cardiomyopathy therapeutics. However, estimates of cardiomyocyte turnover rates conflict greatly, with a study employing C14 pulse-chase methodology concluding 1% annual turnover in youth declining to 0.5% with aging and another using cell population dynamics indicating substantial, age-increasing turnover (4% increasing to 20%).ObjectiveCreate a hybrid mathematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Telomere shortening occurs when proliferating cells undergo each cell cycle, finally leading to cell senescence and apoptosis . However, the role of telomere attrition in the setting of HF and specifically in human cardiomyocytes, classically known as post‐mitotic cells, is undefined. To investigate TL in HCM cardiomyocytes, human cardiac tissues from patients with HCM and NFDs were subjected to Q‐FISH (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Telomere shortening occurs when proliferating cells undergo each cell cycle, finally leading to cell senescence and apoptosis . However, the role of telomere attrition in the setting of HF and specifically in human cardiomyocytes, classically known as post‐mitotic cells, is undefined. To investigate TL in HCM cardiomyocytes, human cardiac tissues from patients with HCM and NFDs were subjected to Q‐FISH (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…AMS provides a tissue-average, which poses a challenge since in cardiomyocytes, S-phase can be connected with cell division and differentiation. Hence, the analysis relied on additional assumptions that had to be made for mathematical modeling of the data (22), including assumptions about potential changes of the number of cardiomyocytes after birth, rates of cardiomyocyte cell death, and the extent of non-proliferative cell cycles (multinucleation and ploidy) with age (23). …”
Section: Classical and New Methods Have Advanced Cardiac Regenerationmentioning
confidence: 99%
“…Moreover, these rates of cardiac myocyte formation via 14 C incorporation are highly dependent on assumptions and parameters used in the mathematical models. Independent analysis of these data has suggested that variations in parameters such as atmospheric 14 C levels or myocyte attrition rates can confound the interpretation of human cardiomyogenesis via 14 C incorporation 68 . The modeling approaches using 14 C incorporation also concluded that new myocyte formation ceases in the early postnatal human heart, whereas other studies have documented indices of myocyte proliferation in young human heart tissues 69 , albeit only at the post-mortem histological level.…”
Section: New Myocyte Formation Across Development Homeostasis and Imentioning
confidence: 99%